Insights into the desulfurization mechanism of low-grade limestone as absorbent induced by particle size. (1st December 2021) - Gu, Shuaiwei; Yang, Zhizhong; Chen, Zhen; Wang, Haiming; Liu, Hanzi; Zhang, Wei; You, Changfu
Graphical abstract: Highlights: Low-grade limestone (LGL) is evaluated as an alternative absorbent in WFGD process. Dissolution kinetics for LGL with different particle sizes are determined. The reaction process and desulfurization mechanism of LGL are proposed. Abstract: Utilization of low-grade limestone (LGL) in wet flue gas desulfurization (WFGD) has been considered as a promising technology due to the decrease in limestone grade caused by the overexploitation of natural high-grade limestone. In this study, the dissolution kinetics and desulfurization mechanism of LGL absorbents induced by particle size were investigated. Shrinking core kinetic model (SCKM) was employed to study the complete dissolution kinetic analysis. The results showed that the dissolution of LGL was controlled by the diffusion through an inert solid film composed of the residue CaMg(CO3 )2, which was insensitive to the variation of particle size. Finer LGL particles having higher dissolution rate and stronger Ca 2+ ions releasing ability exhibited a better desulfurization performance. The spent absorbents and reacted liquid phase products were analyzed by X-Ray diffraction (XRD) analysis, scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and inductively coupled plasma luminescence spectrometry (ICP-OES). These characterizations illustrated that it was primarily CaCO3 in LGL which had a much higher desulfurization capacity that removed SO2 in the beginning. The solid film formed during the desulfurization process was thinner for fine LGL compared with that of coarse LGL. Furthermore, the desulfurization product mainly consisted of gypsum and the decrease in LGL particle size can greatly enhance the gypsum crystal formation. These investigations are of significant importance for providing insights to improve WFGD efficiency with the utilization of low-grade limestone.